The perspectives of patients with depression toward esketamine, and the influence of their medication adherence on their viewpoints: a Saudi cross-sectional study - Almadani, Ahmad H.; Alghamdi, Ayedh H.; Alfahad, Fahad B.; Alibrahim, Abdullah S.; Binbakhit, Abdulrahman I.; Alenazi, Ziyad B.; Alruwaili, Lama M.; Alshahwan, Abdulrahman A.; Muhnna, Abdullah K.; Aljaffer, Mohammed A. (Frontiers in Psychiatry, 2025)
BackgroundNasal esketamine has demonstrated efficacy in the management of treatment-resistant depression and psychiatric emergency due to major depression. This study investigates acceptance and awareness of esketamine as a depression treatment option, focusing on factors that influence patients’ acceptance, including adherence to current medication regimens, regardless of prior esketamine exposure.MethodsThis cross-sectional study surveyed 283 adults with depression using a questionnaire and the Medication Adherence Rating Scale (MARS-10).Results52.3% of participants were willing to receive esketamine, and 51.2% preferred its weekly or biweekly dosing over daily antidepressants; 79.5% reported cost as a potential barrier. Common concerns included medication unavailability (59.7%), fear of addiction (50.5%), anticipated stigma (24.4%), and first-month dosing frequency (21.2%). Regarding adherence, 77.4% were nonadherent to their current psychiatric medication regimen. Adherence to the current regimen was higher among patients with previous esketamine use (p <.001) and among those who had someone to stay with them during and after treatment (p = .047).ConclusionPatients are open to esketamine but have concerns that must be addressed. It also highlights non-adherence as a significant issue in patients with depression. These findings highlight the importance of patients’ education, family involvement, and logistical supports.